Synthesis of (+)-lentiginosine and its pyrrolizidine analogue based on intramolecular cyclization of α-sulfinyl carbanions - Sakkarin Du-A-Man (2018)
A synthesis of (+)-lentiginosine and its pyrrolizidine analogue was accomplished in six steps, starting from L-(+)-tartaric acid. The key step of these syntheses involves the intramolecular cyclization of α-sulfinyl carbanions for the construction of the indolizidine or pyrrolizidine ring. Copyright © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.